Tingkat Motivasi Belajar Mahasiswa dalam Pembelajaran Mata Kuliah Kemampuan Dasar Mengajar - Pradipta, Anangga Widya; Hartati, Tri Asih Wahyu; Istiawan, Nurcholis; Muarifudin, Moh. Ali (FKIP Universitas Wisnuwardhana, 2022)
This study aims to measure the level of student’s learning motivation in Basic Teaching Skills course. Descriptive quantitative method was applied in this study, in which the numerical data were presented in descriptive form. The Likert-scale was used to measure the questionnaire as the instrument of this study. Findings showed that according to the result of motivation scale table, it could be stated that the students were in a ‘very good’ category of learning motivation. In details, the average score for each question item was 65.81, which determined as ‘very good’. While the average score for the whole question items was 156.85, considered as ‘very good’. Along with that, the highest score was found in question number 42 (score 80 and categorized as ‘very good’), while the lowest score was in question item 35 (score 41 and categorized as ‘enough’). Thus, in reference to the statement of the questionnaire, it was fair to say that students were genuinely happy and excited in learning Basic Teaching Skills despite the fact that they found it worthless for current and future situation.